(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2024)
Integrating Building Information Modeling (BIM) into civil engineering represents a transformative shift in the educational and professional landscape. This paper explores the potential of BIM as a catalyst for enhancing civil engineering skills development. The participants were 51 students enrolled in the civil engineering department at the National Institute of Construction Technology and Management, Uromi, Edo State. The study employed a quasi-experimental approach with two groups. The t-test analysis revealed a significant difference in civil engineering skills between the experimental and control groups. In conclusion, the paper posits that BIM is an essential tool in the civil engineer’s repertoire, capable of stimulating significant advancements in skill development, project management, and collaborative work. By leveraging BIM’s capabilities, educators and industry professionals can foster a more dynamic learning environment and prepare the next generation of engineers for the complexities of modern infrastructure projects.